2018
DOI: 10.1080/13573322.2018.1441145
|View full text |Cite
|
Sign up to set email alerts
|

Capoeira for beginners: self-benefit for, and community action by, new Capoeiristas

Abstract: Capoeira could be defined as a Brazilian martial art and game to be played. This research explored how capoeira play might be considered to facilitate connectedness amongst newlyrecruited persons, plus any other ramifications of capoeira involvement. A beginners' course of capoeira was provided to participants, free of charge, in an English city in the West Midlands -new capoeiristas in a new venue for capoeira. Researchers attended classes to collect/construct overt non-participant observation data. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…This study supports these prior assertions, where participants found the capoeira training program to be an exciting and enjoyable experience. The findings of this study support the utility of the capoeira training program for youth with VI, which may make this Afro-Brazilian martial dance (Jordan et al, 2019) a viable option to implement elsewhere for this population. Through the current inquiry, we identified some important considerations for designing such programs.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…This study supports these prior assertions, where participants found the capoeira training program to be an exciting and enjoyable experience. The findings of this study support the utility of the capoeira training program for youth with VI, which may make this Afro-Brazilian martial dance (Jordan et al, 2019) a viable option to implement elsewhere for this population. Through the current inquiry, we identified some important considerations for designing such programs.…”
Section: Discussionsupporting
confidence: 69%
“…The capoeira dance program’s content was designed to create an environment of freedom, social interaction, and enjoyment among participants, instructors, and volunteers (Assunção, 2005, 2014). In keeping with earlier programs designed for beginners, instructors selected capoeira techniques that were most suitable for novice learners and emphasized aspects of capoeira training that were centered most around dance, rather than combat-related strategy (Jordan et al, 2019). Training sessions were held twice per week for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations